Retroesophageal left brachiocephalic vein in an infant without cardiac anomalies - Goel, Alexander N.; Reyes, Camila; Mclaughlin, Shauna; Wittry, Mark; Fiore, Andrew C. (Prenatal Cardiology, 2016)
Retroesophageal course of the left brachiocephalic vein is a rare variant seen in patients with congenital heart disease. However, this anomaly without associated cardiac or aortic abnormalities is nearly unheard of, with only one prior case described in the literature. We present an infant with anomalous retroesophageal left brachiocephalic vein that was an incidental finding on computed tomography (CT). We also briefly discuss its embryologic and clinical significance.